Exploring Barriers to Medication Safety in an Ethiopian Hospital Emergency Department: A Human Factors Engineering Approach - Ephrem Abebe; Michelle A. Chui (University of Minnesota Libraries Publishing, 2018)
Objective: To describe challenges associated with the medication use process and potential medication safety hazards in an Ethiopian hospital emergency department using a human factors approach. Methods: We conducted a qualitative study employing observations and semi-structured interviews guided by the Systems Engineering Initiative for Patient Safety model of work system as an analytical framework. The study was conducted in the emergency department of a teaching hospital in Ethiopia. Study participants included resident doctors, nurses, and pharmacists. We performed content analysis of the qualitative data using accepted procedures. Results: Organizational barriers included communication failures, limited supervision and support for junior staff contributing to role ambiguity and conflict. Compliance with documentation policy was minimal. Task related barriers included frequent interruptions and work-related stress resulting from job requirements to continuously prioritize the needs of large numbers of patients and family members. Person related barriers included limited training and work experience. Work-related fatigue due to long working hours interfered with staff's ability to document and review medication orders. Equipment breakdowns were common as were non-calibrated or poorly maintained medical devices contributing to erroneous readings. Key environment related barriers included overcrowding and frequent interruption of staff's work. Cluttering of the work space compounded the problem by impeding efforts to locate medications, medical supplies or medical charts. Conclusions: Applying a systems based approach allows a context specific understanding of medication safety hazards in EDs from low-income countries. When developing interventions to improve medication and overall patient safety, health leaders should consider the interactions of the different factors. Conflict of Interest We declare no conflicts of interest or financial interests that the authors or members of their immediate families have in any product or service discussed in the manuscript, including grants (pending or received), employment, gifts, stock holdings or options, honoraria, consultancies, expert testimony, patents and royalties". Treatment of Human Subjects: IRB review/approval required and obtained   Type: Original Research